THE PROTECTION OF STATELESS CHILDREN UNDER THE INSTRUMENTS OF INTERNATIONAL LAW - Ghozali, Falah Al (Universitas Muhammadiyah Mataram, 2023)
Having a clear citizenship status facilitates children in leading their lives and asserting their rights, such as gaining access to education, healthcare, engaging in political activities, and even starting families. However, Institute on Statelessness and Inclusion, located in the Netherlands, estimates that every 10 (ten) minutes, a child is born without nationality in a country in this world. Stateless children face various different challenges. Statelessness hinders their ability to realize their potential and can have adverse effects on social cohesion and stability. In some cases, it can even lead to social tensions and displacement. The researchers used a normative research method in conducting this study. Additionally, the data analysis technique applied is qualitative descriptive, which portrays phenomena and findings related to stateless children, their causes, and their protection within international instruments. In other words, this research shows how the protection of stateless children is viewed from the perspective of international law.